Between Vycyleviski and Germonski - mahmoud, Eid (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Researchers and critics focus on the French comparative research, which is clear and requires no proof. But perhaps we need to be steadfast by the Russian thinkers and critics. The research attempts to complete the opening of some neglected windows with the intent or purpose of extrapolating and checking the situation that we are repressing through the prelude to the confidence of the ideas and opinions that produced what is known as the Russian comparative trend.